التفسير المتطور لقواعد القانون الدولي الخاص دراسة تحليلية مقارنة في قواعد القانون الدولي الخاص - حسن, أ.د محمد جلال; الله, م.م كانياو احمد فتح (Sulaimani Journal for Humanities, 2023)
The legal rule is a social rule of behavior that changes with the change of time and place, which calls for a new reading of the text so that it keeps pace with the alopecia developments in the group. And since the issue of amending laws is not an easy matter that requires procedures, the best way to properly apply these rules is the evolving interpretation of legal rules, given the lack of independent regulation of the rules of private international law, and the Iraqi legislator’s failure to keep pace with the development that accompanied issues (conflict of laws _ and conflict of international jurisdiction) and was limited Based on the rules that came within the scope of Civil Law No. (40) of 1951, the judiciary is required to seek the help of an advanced interpretation of the existing rules in order to be able to adapt them to the changing reality.